2020
DOI: 10.1002/lary.28745
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Effect of Amniotic Membrane in Laryngeal Defects in Rabbit Model

Abstract: Objective Fibrosis and scar formation following laryngeal repairing is a major concern. This study evaluated the efficacy of applying amniotic membrane (AM) as a biologic dressing to reduce fibrosis and inflammation and promote cartilage repair. Study design Experimental animal study. Methods Nine male white Dutch rabbits were selected. A standard defect (5 mm) was created in right and left thyroid lamina. In the right side, two layers of AM were applied while the left side was kept intact for future compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This study utilized some previously described non-MRI methods to evaluate animal cartilage regeneration. 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study utilized some previously described non-MRI methods to evaluate animal cartilage regeneration. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Fibrosis was assessed by the thickness of fibrous tissue on the micrometer scale in the defect area. 22 , 37 Histologic examination was done by an expert pathologist masked as to the treatment side. Histologic criteria grading is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The AMSCs possess unique characteristics that render them useful in diverse applications for tissue repair. These include using as cartilage grafts for tracheal reconstruction of the fetus [ 51 , 52 ], restoration for the diaphragm muscles [ 53 , 54 ], bone grafts [ 55 , 56 ], and heart valve leaflets [ 57 59 ]. Furthermore, seeding human AMSCs in gelatin microcarriers could successfully generate modular bone-like tissues upon osteogenic differentiation [ 60 ].…”
Section: Cellular Components Of the Amnio-mmentioning
confidence: 99%
“…Various treatment modalities, materials, and drugs have been introduced to facilitate laryngeal cartilaginous healing and prevent complications. Several clinical and experimental studies have shown different degrees of success and limitations of these treatment modalities, such as the use of amniotic membrane (AM), 2 adipose‐derived stem cells (ASCs), 3 seeded scaffolds, 4 and platelet‐rich plasma (PRP) 5 in laryngeal defects repair.…”
Section: Introductionmentioning
confidence: 99%
“…as the use of amniotic membrane (AM), 2 adipose-derived stem cells (ASCs), 3 seeded scaffolds, 4 and platelet-rich plasma (PRP) 5 in laryngeal defects repair.…”
mentioning
confidence: 99%